The Description of Internet Game Online Addiction Among Teenagers - Novilia Anggraeni; Hendriati Agustiani; Langgersari Elsari Novianti; Retno Hanggarani Ninin (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
Online game is one of the most popular leisure activity for adolescents. Playing it excessively can lead to addiction. Once addicted, behavior problems arise and at a certain level of addiction, psychological treatment will be needed. The aim of this study is to describe online gaming addiction in terms of four levels of addiction. The participants are 41 high school students (12-14 years old) who lived in Jatinangor. They are active players in online games using mobile phones, computers, or other media. Data were collected using an open-ended questionnaire than qualitatively analysed by the way of thematic analysis. Result shows that participants mostly perceived playing online games as a pleasurable and rewarding activity (recreational level of addiction). In this level, there are negative impacts that occur when they are playing online games, but the impacts disappear when they stop playing an online game. In at-risk level, participants feeling the rewarding effects (e.g. stress release). Participants accept when their parents start complaining about their gaming behavior. In problematic use level, the gaming behavior is increasingly done alone and often dismissed parents’ concern about their gaming behavior. In fully addict level, only the amount of time for playing online games reported (8 hours per day). Keywords: addiction, game online, adolescence, online mobile gaming